Ambientes virtuais institucionais e não institucionais: estudo de caso com professores de uma instituição de ensino superior salesiana - Bento, Maria Cristina Marcelino (2016)
This doctoral thesis explores the use of Virtual Learning Environments (VLE) in education. It is a case study in a Salesian institution of higher education located in the state of São Paulo (Brazil). The case study outlines in qualitative research (BOGDAN; BIKLEN, 1994; YIN, 2015) comprising three stages: exploration, data collection and analysis. Its objectives are to describe and analyze how a group of teachers of this institution uses institutional and non-institutional virtual environments, identify and justify the use of non-institutional virtual environments and observe the differences in the use of institutional and non-institutional environments. Moodle and Facebook are the virtual environments used by teachers in the institution. The study noted that the use of weighted form occurs in both environments, as the process of understanding and\or learning environment of each tool, the adequacy to the profile of the students, or the need to understand their own role in cyberspace. The analysis concludes that there is need for change of the pedagogical practice for teachers using AVA as an extension of the classroom, which affects the teaching profile